Advances in Applied Biotechnology Proceedings of the 3rd International Conference on Applied Biotechnology (ICAB2016), November 25-27, 2016, Tianjin, China (Lecture Notes in Electrical Engineering,, 2018)
This book presents and discusses the latest advances in biotechnology, and selected challenges and opportunities in connection with its industrial applications. It gathers the proceedings of the 3rd International Conference on Applied Biotechnology (ICAB2016), held on November 25-27, 2016 in Tianjin, China, which continued the success of the previous biennial ICAB conferences, providing a platform for scientists and engineers to exchange ideas about the frontiers of biotechnology. Topics include (but are not limited to) microbial genetics and breeding; biological separation and purification; optimization and control of biological processes; and advances in biotechnology. Offering key insights into the latest breakthroughs, the book is intended for industrial leaders, professionals and research pioneers in the field of applied biotechnology.